The Feldstein-Horioka Hypothesis in Countries with Varied Levels of Economic Development - Piotr Misztal (Contemporary Economics)
This article aims to analyse the Feldstein-Horioka hypothesis, which suggests a strong correlation between investments and savings in advanced economies. Additionally, the analysis of the Feldstein- Horioka hypothesis was expanded to include emerging markets and developing economies in order to provide a thorough analysis of this issue.1 The paper utilises a research method based on bibliographic studies in macroeconomics and international finances as well as econometric methods (the vector autoregressive model - VAR). All statistical data used in the paper are taken from the statistical database of the International Monetary Fund (World Economic Outlook Database).